Self-cleaning rock flake real stone paint and preparation method thereof

Through the use of high -surface potassium silicate and lithium silicate silica or silicon dioxide microspheres in real stone paint, combined with high surface energy of pure propyleca emulsion, giving coatings to super -consuming water and super sparse oil underwater oil oil Performance solves the problem of being easily polluted in the long -term exposure of traditional real stone paint, and realizes self -cleaning function and durability improvement.

CN116375396BActive Publication Date: 2025-01-24TIANJIN DEPUWEI COATINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310371750.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-10
Publication Date
2025-01-24
Estimated Expiration
2043-04-10

AI Technical Summary

Technical Problem

Traditional real stone paint is susceptible to pollution when exposed to the atmosphere for a long time, resulting in reduced decoration effect, accelerated aging and increased maintenance costs.

Method used

Using high -surface energy with potassium silicate and lithium silicate to form polyshicate or silicon microspheres in real stone lacquer base materials, combined with high surface energy of pure propylecal lotion, giving coatings super -proof water and underwater ultra -oil sparse oil Performance, realize self -cleaning function, and promote the adhesion of the coating through the sodium boronic acid solution.

Benefits of technology

It improves the stain resistance and durability of real stone paint, realizes self-cleaning function, reduces the risk of dirt adhesion and aging and decomposition, and extends the service life of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004168825990000141
    Figure BDA0004168825990000141
  • Figure BDA0004168825990000151
    Figure BDA0004168825990000151
Patent Text Reader

Abstract

The present application discloses a self-cleaning rock flake real stone paint and a preparation method thereof. The real stone paint comprises white sand, colored sand, rock flakes and a base material, wherein the base material comprises: 340-354 parts of water, 1.2-1.8 parts of bentonite, 2-3 parts of hydroxyethyl cellulose, 0.2-0.8 parts of multifunctional additives, 0.8-1.2 parts of kason fungicide, 4-8 parts of antifreeze, 100-160 parts of pure acrylic emulsion, 6-12 parts of film-forming additives, 0.2-0.8 parts of defoaming agent, 2.5-3.5 parts of thickener, 1-1.6 parts of wetting agent, 15-20 parts of potassium silicate, 5-7 parts of lithium silicate, and 3-5 parts of 4-5wt% sodium tetraborate solution. The real stone paint of the present application has super hydrophilic and underwater super oleophobic properties, which can block most of the dirt from adhering to the coating surface. At the same time, it can also use rainwater to wash away the dirt, thus realizing the self-cleaning function, having strong stain resistance and high durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of real stone paint coatings, and more specifically, to a self-cleaning rock flake real stone paint and a preparation method thereof. Background Art

[0002] Real stone paint is a kind of paint with decorative effect similar to marble and granite. It is mainly made of natural stone powder of various colors. It has strong decorative effect and the texture of natural stone. The design of various lines and grids can provide various three-dimensional pattern structures. It is widely used on the exterior walls of buildings to imitate stone. It is the best substitute for dry hanging stone on the exterior wall. However, traditional real stone paint has the disadvantages of large specific gravity, high energy consumption and serious waste of resources. Therefore, rock flake real stone paint is now mostly used to replace traditional real stone paint.

[0003] Rock flake real stone paint is made of natural colored sand, water-based polymer resin and rock flakes in a certain proportion. When using it, you should first analyze the main color of the natural granite stone to be imitated, and choose the real stone paint made from natural colored sand close to the main color. Then, according to the color, size and proportion of the colored particles in the stone, choose rock flakes, add them to the prepared real stone paint, stir evenly, and spray them on the exterior wall of the building to obtain a colorful granite effect. Rock flake real stone paint has excellent water resistance and weather resistance, and is easy to apply, which greatly shortens the construction time, saves construction costs, and reduces construction energy consumption. It is a green, energy-saving and environmentally friendly product with excellent performance.

[0004] However, since the rock flake real stone paint is applied on the surface of the exterior wall, it will be exposed to the atmosphere for a long time and polluted by various substances. The pollution sources include a large amount of dust, solid fog and smoke and other solid substances, liquid substances such as sulfuric acid mist, gaseous substances such as sulfur dioxide, and microorganisms, rust and water dripping and other pollution will also affect the exterior wall. On the one hand, the pollution of the exterior wall will affect the decorative effect and beauty of the building, reduce the gloss and brightness of the coating, and form gray spots, tear spots and other marks; on the other hand, certain pollutants will accelerate the aging and decomposition of the coating, affect the service life and safety of the building, and increase the cleaning and maintenance costs of the building. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a self-cleaning rock flake real stone paint and a preparation method thereof.

[0006] In the first aspect, the present application provides a self-cleaning rock flake real stone paint, which adopts the following technical solution:

[0007] A self-cleaning rock flake real stone paint comprises white sand, colored sand, rock flakes and a base material in a weight ratio of (350-450):(45-50):(45-55):(480-520); in parts by weight, the base material comprises: 340-354 parts of water, 1.2-1.8 parts of bentonite, 2-3 parts of hydroxyethyl cellulose, 0.2-0.8 parts of a multifunctional additive, 0.8-1.2 parts of a kasson fungicide, 4-8 parts of an antifreeze agent, 100-160 parts of a pure acrylic emulsion, 6-12 parts of a film-forming additive, 0.2-0.8 parts of a defoaming agent, 2.5-3.5 parts of a thickener, 1-1.6 parts of a wetting agent, 15-20 parts of potassium silicate, 5-7 parts of lithium silicate, and 3-5 parts of a 4-5wt% sodium tetraborate solution.

[0008] By adopting the above technical scheme, the application adds potassium silicate and lithium silicate with high surface energy to the base material of real stone paint, and forms many densely distributed polysilicates or silicon dioxide microspheres on the coating surface by using the silicate condensation reaction occurring between the two. According to the special wettability principle, these nanometer-level roughnesses are matched with hydrophilic components with high surface energy such as pure acrylic emulsion, and the performance of super-hydrophilic and underwater super-oleophobic coating can be given, and the water film sliding layer generated by the hydrophilic groups on the coating surface in combination with water molecules can block most of the dirt from adhering to the coating surface, and the sliding of the water film can also be used to remove dirt, so that the real stone paint has the function of self-cleaning, and the anti-fouling ability of the real stone paint is effectively improved. At the same time, the potassium silicate and lithium silicate of the present application, under the promotion of sodium tetraborate solution, condensation reaction will continue to occur, and finally a silica gel network structure with a higher degree of crosslinking is formed inside the real stone paint, which enhances the adhesion of the coating, thereby improving the durability of the real stone paint.

[0009] Preferably, in parts by weight, the base material includes: 347 parts of water, 1.5 parts of bentonite, 2.5 parts of hydroxyethyl cellulose, 0.5 parts of multifunctional additive, 1 part of Kathon fungicide, 6 parts of antifreeze, 130 parts of pure acrylic emulsion, 8 parts of film-forming additive, 0.5 parts of defoaming agent, 3 parts of thickener, 1.3 parts of wetting agent, 18 parts of potassium silicate, 6 parts of lithium silicate, and 4 parts of 4-5wt% sodium tetraborate solution.

[0010] By adopting the above technical scheme, the present application further controls the usage amount of raw materials used in the real stone paint, and can further improve the stain resistance and durability of the real stone paint.

[0011] Preferably, the base material further comprises 7-10 parts by weight of nano zinc oxide and 8-10 parts by weight of nano aluminum oxide.

[0012] By adopting the above-mentioned technical scheme, the present application also embeds nano zinc oxide and nano aluminum oxide with high surface energy into the internal network structure of the real stone paint, thereby increasing the number of nanoparticles on the coating surface and improving the density of the nanoparticles on the coating surface, thereby further improving the stain resistance and durability of the real stone paint.

[0013] Preferably, the pure acrylic emulsion is prepared by the following method:

[0014] (1) dissolving 4.5-5.0 parts by weight of an emulsifier in 15-16 parts by weight of water, then adding 28-30 parts by weight of methyl methacrylate, 59-61 parts by weight of butyl acrylate, 2-3 parts by weight of acrylic acid, 6-7 parts by weight of diethylene glycol diacrylate and 3-4 parts by weight of hydroxyethyl acrylate, and continuing to stir for 30-40 minutes until a milky white pre-emulsion is obtained; dissolving 0.4-0.5 parts by weight of potassium persulfate in water to obtain a potassium persulfate solution;

[0015] (2) dissolving 2-3 parts by weight of NaHCO3 in water and heating the mixture to 45-50°C, then adding a pre-emulsion and a potassium persulfate solution, continuing to heat the mixture to 75-80°C, and stirring the mixture for 30-40 minutes; the amount of the pre-emulsion being 10-12% of the total amount of the pre-emulsion obtained in step (1), and the amount of the potassium persulfate solution being 45-50% of the total amount of the potassium persulfate solution obtained in step (1);

[0016] (3) At a temperature of 75-80° C., the remaining amount of the pre-emulsion and potassium persulfate solution are added dropwise to the resultant of step (2) within 1-1.5 hours, and then the temperature is raised to 85-90° C. and the reaction is kept warm for 1-1.2 hours, then cooled to room temperature, filtered, and the pH value is adjusted to 8-9 with aqueous ammonia to obtain a pure acrylic emulsion.

[0017] Since the white sand and colored sand used in this application are mostly fine powders of about 200 meshes in order to improve the hiding power of real stone paint, this fineness of white sand and colored sand is very easy to be slowly brought to the surface of real stone paint by rain over time to form exudative pollution. Therefore, by adopting the above technical scheme, this application adopts a semi-continuous pre-emulsification process, with methyl methacrylate as a hard monomer, butyl acrylate as a soft monomer, and acrylic acid, diethylene glycol diacrylate, and hydroxyethyl acrylate as a functional monomer and a cross-linking monomer, to prepare a pure acrylic emulsion with strong film-forming property, stability, water resistance, wear resistance, hardness, tensile strength, adhesion, solvent resistance and oil resistance, which can form a good package for white sand, colored sand and rock flakes, reducing the possibility of exudative pollution, thereby improving the anti-fouling ability of real stone paint.

[0018] Preferably, the emulsifier comprises an anionic emulsifier and a nonionic emulsifier in a weight ratio of (5-6):(1-2); the anionic emulsifier is sodium salt of alkyl sulfosuccinate, and the nonionic emulsifier is nonionic emulsifier S90.

[0019] By adopting the above technical scheme, the present application adopts a mixture of anionic emulsifiers and nonionic emulsifiers, and adopts sodium salt of alkyl sulfosuccinate as the anionic emulsifier and nonionic emulsifier S90 as the nonionic emulsifier, so as to give full play to the synergistic effect of the two, further improve the hydrophilicity of the pure acrylic emulsion, enhance the wettability of the real stone paint, and make the stains attached to the surface of the real stone paint more easily removed by water, thereby further improving the stain resistance of the real stone paint.

[0020] Preferably, in step (3), before cooling, 1.8-2.0 parts by weight of gelatinized oxidized starch is added, and the reaction is continued at the temperature for 1-1.2 hours.

[0021] By adopting the above technical scheme, the present application heats the oxidized starch in water until the micelle structure completely collapses, the starch molecules form single molecules, and are surrounded by water to become a solution state, and then adds it to the pure acrylic emulsion. The oxidized starch is used to provide more cross-linking points for the pure acrylic emulsion, thereby enhancing the degree of cross-linking inside the pure acrylic emulsion. The oxidized starch particles can also fill the gaps between the polyacrylate chains, thereby improving the density of the network structure of the pure acrylic emulsion, thereby further improving the stain resistance and durability of the real stone paint.

[0022] Preferably, the film-forming aid comprises vegetable oleic acid furfuryl ester and ricinoleic acid ethylene glycol monoester in a weight ratio of 1:(1.2-1.5).

[0023] By adopting the above-mentioned technical scheme, the present application adopts a mixture of vegetable oil furfuryl ester and castor oil glycol monoester as film-forming aids, which can give full play to the synergistic effect between the two, improve the film-forming effect of real stone paint, thereby improving the density of real stone paint, reducing the possibility of pollutants penetrating into the interior of real stone paint, and thus improving the stain resistance of real stone paint.

[0024] Preferably, the vegetable oleic acid furfuryl ester is prepared by the following method:

[0025] Vegetable oleic acid, furfuryl alcohol, cyclohexane, ionic liquid catalyst and sodium hypochlorite are mixed and heated to 80-90°C, kept warm for reaction for 3-3.5 hours, cooled to room temperature, filtered, pH value adjusted to 6-7 with 5-7wt% NaHCO3 solution, allowed to stand for stratification, and decompressed and desolventized the upper oil layer to obtain vegetable oleic acid furfuryl alcohol ester; n(vegetable oleic acid):n(furfuryl alcohol) is 1:(1.2-1.25), and the weight ratio of cyclohexane, ionic liquid catalyst, sodium hypochlorite and vegetable oleic acid is (2.8-3.0):(0.01-0.02):(0.01-0.02):1.

[0026] Preferably, the ricinoleic acid ethylene glycol monoester is prepared by the following method:

[0027] Add ricinoleic acid and a solid acid catalyst to 100-110 parts by weight of toluene, mix and stir for 10-15 minutes, then add ethylene glycol and heat to 87-90°C, react for 4-5 hours, then cool to room temperature, adjust the pH value to 6-7 with 3-4wt% NaHCO3 solution, let stand to separate, decompress the upper oil layer and desolventize to obtain ricinoleic acid ethylene glycol monoester; n(ricinoleic acid):n(ethylene glycol) is 1:(1.2-1.3), and the amount of the solid acid catalyst is 1.8-2wt% of ricinoleic acid.

[0028] In a second aspect, the present application provides a method for preparing a self-cleaning rock flake real stone paint, comprising the following steps:

[0029] S1. The lithium silicate, wetting agent and pure acrylic emulsion are magnetically stirred for 10-15 min, and then potassium silicate is added dropwise and magnetically stirred for 10-15 min, and then mixed with 4-5wt% sodium tetraborate solution and stirred for 20-30 min to obtain a mixed solution;

[0030] S2. Bentonite and hydroxyethyl cellulose are added to water while stirring, and then dispersed at a high speed of 1300-1400r / min for 20-30min, and then the speed is reduced to 500-600r / min, and a multifunctional additive, a kasoon fungicide, an antifreeze agent, a mixed solution of step S1, a film-forming aid and a defoaming agent are added, mixed and stirred for 5-10min, and then a thickener is added, and dispersed at a speed of 800-900r / min for 8-10min to obtain a base material;

[0031] S3. At a rotation speed of 300-310r / min, add white sand, colored sand and rock flakes to the base material of step S2, mix well, and obtain self-cleaning rock flake real stone paint.

[0032] By adopting the above technical solution, the present application adopts step-by-step mixing, so that the components in the real stone paint can be fully mixed, reducing the possibility of agglomeration of the components in the real stone paint, thereby further improving the anti-fouling ability and durability of the real stone paint. In addition, the preparation method of the present application is simple, easy to operate, and the raw materials are easily available, which is suitable for large-scale industrial production.

[0033] Preferably, in step S1, 7-10 parts by weight of nano zinc oxide and 8-10 parts by weight of nano aluminum oxide are also added.

[0034] In summary, this application has the following beneficial technical effects:

[0035] 1. The real stone paint of the present application has super hydrophilic and underwater super oleophobic properties, can prevent most of the dirt from adhering to the coating surface, and can also use rainwater to wash away the dirt attached to the coating surface, realizing the self-cleaning function and having strong stain resistance; 2. The real stone paint of the present application is different from the ordinary super hydrophilic self-cleaning real stone paint, not only has strong self-cleaning ability, but also has high durability, can firmly adhere to the substrate, and reduces the possibility of the real stone paint being separated from the substrate or the surface structure changing and losing the super hydrophilic property;

[0036] 3. The preparation method of the real stone paint of the present application has simple steps, is easy to operate, and has readily available raw materials, and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0038] In the following preparation examples, embodiments and comparative examples,

[0039] White sand is produced in Cicheng, with mesh size of 80-200;

[0040] Colored sand is produced in Cicheng, with a mesh size of 200-300;

[0041] Rock slices were purchased from Jiangxi Tiansheng Chemical Co., Ltd., with a diameter of 1-3 mm;

[0042] Bentonite was purchased from Clemington, model ZW;

[0043] Hydroxyethyl cellulose was purchased from Shandong Yunying, model BR100000H;

[0044] The multifunctional additive was purchased from Solvay, model MP380;

[0045] Kasong fungicide was purchased from Thor, UK, model HF;

[0046] Antifreeze (ethylene glycol) was purchased from Tianjin Haoming Chemical Co., Ltd.;

[0047] The defoamer was purchased from San Nopco, Japan, model SN154;

[0048] The thickener was purchased from Dow, USA, model TT615;

[0049] The wetting agent was purchased from Qingdao Shengshi New Materials Co., Ltd., model RD9125;

[0050] Potassium silicate and lithium silicate were purchased from Shandong Dongyue Chemical Co., Ltd.;

[0051] Sodium tetraborate was purchased from Langfang Qianyao Technology Co., Ltd.;

[0052] Nano zinc oxide was purchased from Zhuozhou Yourong New Material Technology Co., Ltd.;

[0053] Nano-alumina was purchased from Dongguan Dongchao New Materials Technology Co., Ltd.;

[0054] Methyl methacrylate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0055] Butyl acrylate was purchased from Shandong Huasheng New Materials Co., Ltd.;

[0056] Acrylic acid was purchased from Jinan Chuangshi Chemical Co., Ltd.;

[0057] Diethylene glycol diacrylate was purchased from Guangdong Sanqi New Materials Co., Ltd.;

[0058] Hydroxyethyl acrylate was purchased from Shandong Yaojia Chemical Co., Ltd.;

[0059] Potassium persulfate was purchased from Shandong Xuxiang Chemical Co., Ltd.;

[0060] Sulfosuccinic acid alkyl alcohol ether ester sodium salt was purchased from Shanghai Zhongcheng Fine Chemical Co., Ltd.;

[0061] Nonionic emulsifier S90 (secondary alcohol polyoxyethylene ether) was purchased from San Chemical Technology Co., Ltd.;

[0062] Oxidized starch was purchased from Jiangsu Rayen Environmental Protection Technology Co., Ltd.;

[0063] Vegetable oleic acid was purchased from Jinan Shunwang Chemical Co., Ltd.;

[0064] Furfuryl alcohol was purchased from Shanghai Demo Pharmaceutical Technology Co., Ltd.;

[0065] Ionic liquid catalyst (1-butyl-3-methylimidazole dicyandiamide salt) was purchased from Wuhan Smik Biotechnology Co., Ltd.; sodium hydrosulfite (sodium dithionite) was purchased from Shandong Haideng New Materials Co., Ltd.;

[0066] Ricinoleic acid was purchased from Shandong Tonglan Chemical Co., Ltd.;

[0067] The solid acid catalyst was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd., model HND-8;

[0068] Sodium dodecyl sulfate was purchased from Jinan Hengteng Chemical Co., Ltd.;

[0069] Sodium dodecyl sulfate was purchased from Shandong Ruijiang Chemical Co., Ltd.;

[0070] Sodium alkylphenol ether sulfosuccinate was purchased from Shanghai Zhongcheng Fine Chemical Co., Ltd.;

[0071] The film-forming agent TEXANOL was purchased from Guangzhou Hengyu Chemical Co., Ltd.

[0072] Preparation Example

[0073] Preparation Example 1

[0074] The preparation method of pure acrylic emulsion comprises the following steps:

[0075] (1) dissolving 45 g of an emulsifier (sodium salt of alkyl sulfosuccinate) in 160 g of water, then adding 280 g of methyl methacrylate, 610 g of butyl acrylate, 20 g of acrylic acid, 70 g of diethylene glycol diacrylate and 30 g of hydroxyethyl acrylate, and continuing to stir for 40 min until a milky white pre-emulsion is obtained; adding 4 g of potassium persulfate into the water, and shaking to dissolve to obtain a potassium persulfate solution;

[0076] (2) dissolving 30 g of NaHCO3 in water and heating the mixture to 45° C., then adding the pre-emulsion and potassium persulfate solution, continuing to heat the mixture to 80° C., and stirring the mixture for 30 min; wherein the amount of the pre-emulsion is 12% of the total amount of the pre-emulsion obtained in step (1), and the amount of the potassium persulfate solution is 45% of the total amount of the potassium persulfate solution obtained in step (1);

[0077] (3) At a temperature of 80° C., the remaining amount of the pre-emulsion and potassium persulfate solution are added dropwise to the resultant of step (2) within 1 hour, and then the temperature is raised to 90° C. and the reaction is kept at this temperature for 1 hour. Thereafter, the mixture is cooled to room temperature, filtered, and the pH value is adjusted to 9 with aqueous ammonia to obtain a pure propylene emulsion.

[0078] Preparation Example 2

[0079] The preparation method of pure acrylic emulsion comprises the following steps:

[0080] (1) Dissolve 50 g of emulsifier (nonionic emulsifier S90) in 150 g of water, then add 300 g of methyl methacrylate, 590 g of butyl acrylate, 30 g of acrylic acid, 60 g of diethylene glycol diacrylate and 40 g of hydroxyethyl acrylate, and continue stirring for 30 min until a milky white pre-emulsion is obtained; add 5 g of potassium persulfate into water, shake well to dissolve and obtain a potassium persulfate solution; (2) Dissolve 20 g of NaHCO3 in water and heat to 50° C., then add the pre-emulsion and potassium persulfate solution, continue to heat to 75° C., and stir for 40 min; wherein the amount of the pre-emulsion is 10% of the total amount of the pre-emulsion obtained in step (1), and the amount of the potassium persulfate solution is 50% of the total amount of the potassium persulfate solution obtained in step (1);

[0081] (3) At a temperature of 75° C., the remaining amount of the pre-emulsion and potassium persulfate solution were dropwise added to the resultant of step (2) within 1.5 h, and then the temperature was raised to 85° C. and the reaction was kept warm for 1.2 h. After that, the mixture was cooled to room temperature, filtered, and the pH value was adjusted to 8 with aqueous ammonia to obtain a pure acrylic emulsion.

[0082] Preparation Example 3

[0083] The preparation method of pure acrylic emulsion comprises the following steps:

[0084] (1) 48 g of an emulsifier (nonionic emulsifier S90) was dissolved in 155 g of water, and then 290 g of methyl methacrylate, 600 g of butyl acrylate, 25 g of acrylic acid, 65 g of diethylene glycol diacrylate and 35 g of hydroxyethyl acrylate were added, and stirring was continued for 35 min until a milky white pre-emulsion was obtained; 4.5 g of potassium persulfate was added to the water, and the mixture was shaken and dissolved to obtain a potassium persulfate solution;

[0085] (2) dissolving 25 g of NaHCO3 in water and heating the mixture to 48°C, then adding the pre-emulsion and potassium persulfate solution, continuing to heat the mixture to 78°C, and stirring the mixture for 35 min; wherein the amount of the pre-emulsion is 10% of the total amount of the pre-emulsion obtained in step (1), and the amount of the potassium persulfate solution is 50% of the total amount of the potassium persulfate solution obtained in step (1);

[0086] (3) At a temperature of 78° C., the remaining amount of the pre-emulsion and potassium persulfate solution were dropwise added to the resultant of step (2) within 1.2 h, and then the temperature was raised to 88° C. and the reaction was kept warm for 1.1 h. After that, the mixture was cooled to room temperature, filtered, and the pH value was adjusted to 8 with aqueous ammonia to obtain a pure propylene emulsion.

[0087] Preparation Example 4

[0088] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium salt of alkyl sulfosuccinate and non-ionic emulsifier S90 in a weight ratio of 5:2, wherein the sodium salt of alkyl sulfosuccinate is 34.3 g and the non-ionic emulsifier S90 is 13.7 g.

[0089] Preparation Example 5

[0090] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium salt of alkyl sulfosuccinate and non-ionic emulsifier S90 in a weight ratio of 6:1, wherein the sodium salt of alkyl sulfosuccinate is 41.1 g and the non-ionic emulsifier S90 is 6.9 g.

[0091] Preparation Example 6

[0092] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium salt of alkyl sulfosuccinate and non-ionic emulsifier S90 in a weight ratio of 3:5, wherein the sodium salt of alkyl sulfosuccinate is 18 g and the non-ionic emulsifier S90 is 30 g.

[0093] Preparation Example 7

[0094] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium salt of alkyl sulfosuccinate and non-ionic emulsifier S90 in a weight ratio of 8:1, wherein the sodium salt of alkyl sulfosuccinate is 42.7 g and the non-ionic emulsifier S90 is 5.3 g.

[0095] Preparation Example 8

[0096] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium dodecyl sulfate and nonionic emulsifier S90 in a weight ratio of 5:2, wherein the sodium dodecyl sulfate is 34.3 g and the nonionic emulsifier S90 is 13.7 g.

[0097] Preparation Example 9

[0098] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium dodecyl sulfate and nonionic emulsifier S90 in a weight ratio of 5:2, wherein the sodium dodecyl sulfate is 34.3 g and the nonionic emulsifier S90 is 13.7 g.

[0099] Preparation Example 10

[0100] The difference from Preparation Example 3 is that the emulsifier in step (1) includes sodium alkylphenol ether sulfosuccinate and non-ionic emulsifier S90 in a weight ratio of 5:2, wherein the sodium alkylphenol ether sulfosuccinate is 34.3 g and the non-ionic emulsifier S90 is 13.7 g.

[0101] Preparation Example 11

[0102] The difference from Preparation Example 3 is that in step (3), before cooling, 18 g of gelatinized oxidized starch is added and the reaction is continued at the temperature for 1 hour.

[0103] Preparation Example 12

[0104] The difference from Preparation Example 3 is that in step (3), before cooling, 20 g of gelatinized oxidized starch was added and the reaction was continued at the temperature for 1.2 h.

[0105] Preparation Example 13

[0106] The preparation method of vegetable oleic acid furfuryl ester comprises the following steps:

[0107] Mix 20g of vegetable oleic acid, 8.3g of furfuryl alcohol, 56g of cyclohexane, 0.2g of ionic liquid catalyst and 0.2g of sodium hyposulfite, heat to 90°C, keep warm for 3h, cool to room temperature, filter, adjust the pH value to 6 with 7wt% NaHCO3 solution, let stand to separate, decompress the upper oil layer and desolventize to obtain vegetable oleic acid furfuryl alcohol ester.

[0108] Preparation Example 14

[0109] The preparation method of vegetable oleic acid furfuryl ester comprises the following steps:

[0110] Mix 20g of vegetable oleic acid, 8.67g of furfuryl alcohol, 60g of cyclohexane, 0.4g of ionic liquid catalyst and 0.4g of sodium hyposulfite, heat to 80°C, keep warm for 3.5h, cool to room temperature, filter, adjust the pH value to 7 with 5wt% NaHCO3 solution, let stand to separate, decompress the upper oil layer and desolventize to obtain vegetable oleic acid furfuryl alcohol ester.

[0111] Preparation Example 15

[0112] The preparation method of ricinoleic acid ethylene glycol monoester comprises the following steps:

[0113] 20 g of ricinoleic acid and 0.36 g of a solid acid catalyst were added to 100 g of toluene and stirred for 15 min. Then, 5 g of ethylene glycol was added and the temperature was raised to 87° C. The reaction was continued for 5 h. The mixture was then cooled to room temperature. The pH value was adjusted to 7 using a 3 wt % NaHCO solution. The mixture was allowed to stand for stratification and the upper oil layer was decompressed and desolventized to obtain ethylene glycol ricinoleate.

[0114] Preparation Example 16

[0115] The preparation method of ricinoleic acid ethylene glycol monoester comprises the following steps:

[0116] 20 g of ricinoleic acid and 0.4 g of a solid acid catalyst were added to 110 g of toluene and stirred for 10 min. Then, 5.4 g of ethylene glycol was added and the temperature was raised to 90°C. The reaction was continued for 4 h. The mixture was then cooled to room temperature. The pH value was adjusted to 6 using a 4 wt % NaHCO3 solution. The mixture was allowed to stand for stratification. The upper oil layer was decompressed and desolventized to obtain ethylene glycol ricinoleate.

[0117] Example

[0118] Example 1

[0119] A method for preparing a self-cleaning rock flake real stone paint comprises the following steps:

[0120] S1. 5g of lithium silicate, 1g of wetting agent and 100g of pure acrylic emulsion prepared in Preparation Example 1 were magnetically stirred for 10min, and then 20g of potassium silicate was added dropwise, and magnetically stirred for 15min, and then mixed and stirred with 4wt% sodium tetraborate solution for 30min to obtain a mixed solution; S2. 1.8g of bentonite and 2g of hydroxyethyl cellulose were added to 340g of water while stirring, and then dispersed at a high speed of 1300r / min for 30min, and then the speed was reduced to 500r / min, and 0.8g of multifunctional auxiliary agent, 0.8g of Kathon bactericide, 8g of antifreeze agent, the mixed solution of step S1, 12g of film-forming auxiliary TEXANOL and 0.2g of defoamer were added, mixed and stirred for 10min, and then 3.5g of thickener was added, and dispersed at a speed of 800r / min for 10min to obtain a base material;

[0121] S3. At a rotation speed of 300r / min, add white sand, colored sand and rock flakes to the base material of step S2, mix evenly, and obtain self-cleaning rock flake real stone paint, wherein the weight ratio of white sand, colored sand, rock flakes and base material is 350:50:45:520.

[0122] Example 2

[0123] A method for preparing a self-cleaning rock flake real stone paint comprises the following steps:

[0124] S1. 5.5 g of lithium silicate, 1.2 g of wetting agent and 145 g of pure acrylic emulsion prepared in Preparation Example 2 were magnetically stirred for 13 min, and then 19 g of potassium silicate was added dropwise and magnetically stirred for 12 min, and then mixed with 4.5 wt % sodium tetraborate solution and stirred for 25 min to obtain a mixed solution;

[0125] S2. 1.35 g of bentonite and 2.7 g of hydroxyethyl cellulose were added to 352 g of water while stirring, and then dispersed at a high speed of 1350 r / min for 25 min, then the speed was reduced to 550 r / min, 0.32 g of a multifunctional additive, 0.9 g of a kason bactericide, 7 g of an antifreeze agent, the mixed solution of step S1, 7 g of a film-forming aid TEXANOL and 0.3 g of a defoamer were added, mixed and stirred for 8 min, and then 3.1 g of a thickener was added, and dispersed at a speed of 850 r / min for 9 min to obtain a base material;

[0126] S3. At a rotation speed of 305r / min, add white sand, colored sand and rock flakes to the base material of step S2, mix evenly, and obtain self-cleaning rock flake real stone paint, wherein the weight ratio of white sand, colored sand, rock flakes and base material is 400:50:50:500.

[0127] Example 3

[0128] A method for preparing a self-cleaning rock flake real stone paint comprises the following steps:

[0129] S1. 7 g of lithium silicate, 1.6 g of wetting agent and 160 g of pure acrylic emulsion prepared in Preparation Example 3 were magnetically stirred for 15 min, and then 15 g of potassium silicate was added dropwise and magnetically stirred for 10 min, and then mixed with 5 wt % sodium tetraborate solution and stirred for 20 min to obtain a mixed solution;

[0130] S2. 1.2 g of bentonite and 3 g of hydroxyethyl cellulose were added to 354 g of water while stirring, and then dispersed at a high speed of 1400 r / min for 20 min, then the speed was reduced to 600 r / min, 0.2 g of multifunctional additive, 1.2 g of Kasson bactericide, 4 g of antifreeze, the mixed solution of step S1, 6 g of film-forming aid TEXANOL and 0.8 g of defoamer were added, mixed and stirred for 5 min, and then 2.5 g of thickener was added, and dispersed at a speed of 900 r / min for 8 min to obtain a base material;

[0131] S3. At a rotation speed of 310r / min, add white sand, colored sand and rock flakes to the base material of step S2, mix evenly, and obtain self-cleaning rock flake real stone paint, wherein the weight ratio of white sand, colored sand, rock flakes and base material is 450:45:55:480.

[0132] Example 4

[0133] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the amount of water is 347g, the amount of bentonite is 1.5g, the amount of hydroxyethyl cellulose is 2.5g, the amount of multifunctional additive is 0.5g, the amount of Kathon fungicide is 1g, the amount of antifreeze is 6g, the amount of pure acrylic emulsion is 130g, the amount of film-forming aid TEXANOL is 8g, the amount of defoamer is 0.5g, the amount of thickener is 3g, the amount of wetting agent is 1.3g, the amount of potassium silicate is 18g, the amount of lithium silicate is 6g, and the amount of sodium tetraborate solution is 4g.

[0134] Example 5

[0135] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the amount of wetting agent used is 1.3g, the amount of potassium silicate used is 18g, the amount of lithium silicate used is 6g, and the amount of sodium tetraborate solution used is 4g.

[0136] Example 6

[0137] A method for preparing a self-cleaning rock flake real stone paint is different from that of Example 2 in that: in step S1, after adding the sodium tetraborate solution, 7g of nano zinc oxide and 10g of nano aluminum oxide are also added.

[0138] Example 7

[0139] A method for preparing a self-cleaning rock flake real stone paint is different from that of Example 2 in that: in step S1, after adding the sodium tetraborate solution, 10 g of nano zinc oxide and 8 g of nano aluminum oxide are also added.

[0140] Example 8

[0141] A method for preparing a self-cleaning rock flake real stone paint is different from that of Example 2 in that: in step S1, after adding the sodium tetraborate solution, 5g of nano zinc oxide and 15g of nano aluminum oxide are also added.

[0142] Example 9

[0143] A method for preparing a self-cleaning rock flake real stone paint is different from that of Example 2 in that: in step S1, after adding the sodium tetraborate solution, 18g of nano zinc oxide and 1g of nano aluminum oxide are also added.

[0144] Example 10

[0145] A method for preparing a self-cleaning rock flake real stone paint is different from that of Example 2 in that: in step S1, after adding the sodium tetraborate solution, 7g of nano zinc oxide and 10g of nano titanium dioxide are also added.

[0146] Embodiment 11

[0147] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 4.

[0148] Example 12

[0149] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 5.

[0150] Example 13

[0151] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 6.

[0152] Embodiment 14

[0153] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 7.

[0154] Embodiment 15

[0155] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 8.

[0156] Example 16

[0157] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 9.

[0158] Embodiment 17

[0159] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 10.

[0160] Embodiment 18

[0161] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 11.

[0162] Embodiment 19

[0163] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that the pure acrylic emulsion adopts the pure acrylic emulsion prepared in Preparation Example 12.

[0164] Embodiment 20

[0165] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the film-forming aid includes vegetable oil furfuryl ester prepared in Preparation Example 13 and castor oil glycol monoester prepared in Preparation Example 15 in a weight ratio of 1:1.2, wherein vegetable oil furfuryl ester is 3.18g and castor oil glycol monoester is 3.82g.

[0166] Embodiment 21

[0167] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the film-forming aid includes vegetable oil furfuryl ester prepared in Preparation Example 14 and castor oil glycol monoester prepared in Preparation Example 16 in a weight ratio of 1:1.5, wherein vegetable oil furfuryl ester is 2.8g and castor oil glycol monoester is 4.2g.

[0168] Embodiment 22

[0169] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the film-forming aid includes TEXANOL and ethylene glycol monoester of ricinoleic acid in a weight ratio of 1:1.5, wherein TEXANOL is 2.8g and ethylene glycol monoester of ricinoleic acid is 4.2g.

[0170] Embodiment 23

[0171] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the film-forming aid includes vegetable oil furfuryl ester and ricinoleic acid ethylene glycol monoester in a weight ratio of 2:1, wherein vegetable oil furfuryl ester is 4.67g and ricinoleic acid ethylene glycol monoester is 2.33g.

[0172] Embodiment 24

[0173] A method for preparing a self-cleaning rock flake real stone paint, which is different from Example 2 in that: the film-forming aid includes vegetable oil furfuryl ester and ricinoleic acid ethylene glycol monoester in a weight ratio of 1:3, wherein the vegetable oil furfuryl ester is 1.75g ​​and the ricinoleic acid ethylene glycol monoester is 5.25g.

[0174] Comparative Example

[0175] Comparative Example 1

[0176] The difference from Example 2 is that step S1 is removed, pure acrylic emulsion is added between the antifreeze agent and the film-forming aid, and the rest is the same.

[0177] Comparative Example 2

[0178] The difference from Example 2 is that the pure acrylic emulsion adopts the pure acrylic emulsion produced by Showa of Japan, model 4765, and the rest are the same.

[0179] Comparative Example 3

[0180] The difference from Example 2 is that in step S1, potassium silicate is not added, and the rest is the same.

[0181] Comparative Example 4

[0182] The difference from Example 2 is that in step S1, lithium silicate is not added, and the rest is the same.

[0183] Comparative Example 5

[0184] The difference from Example 2 is that the potassium silicate in step S1 is replaced by sodium silicate, and the rest is the same.

[0185] Comparative Example 6

[0186] The difference from Example 2 is that the lithium silicate in step S1 is replaced by sodium silicate, and the rest is the same.

[0187] Comparative Example 7

[0188] The difference from Example 2 is that the methyl methacrylate in the pure acrylic emulsion prepared in Preparation Example 2 is replaced by methyl acrylate, and the rest is the same.

[0189] Comparative Example 8

[0190] The difference from Example 2 is that the butyl acrylate in the pure acrylic emulsion prepared in Preparation Example 2 is replaced by ethyl acrylate, and the rest is the same.

[0191] Comparative Example 9

[0192] The difference from Example 2 is that the diethylene glycol diacrylate in the pure acrylic emulsion prepared in Preparation Example 2 is replaced by diethylene glycol dimethacrylate, and the rest is the same.

[0193] Performance Testing

[0194] The self-cleaning rock flake true stone paints prepared in Examples 1-24 and Comparative Examples 1-9 were sprayed on panels according to the method specified in JG / T 24-2018 "Synthetic Resin Emulsion Sand Wall Architectural Coatings", and cured under standard conditions for 14 days. Then, the following performance tests were performed on the panels of Examples 1-24 and Comparative Examples 1-9, and the results are shown in Table 1;

[0195] 1. Anti-fouling performance

[0196] Refer to 5.5 immersion method in GB / T 9780-2013 "Test method for stain resistance of architectural coatings". In order to make the test results comparable, the reflection coefficient reduction rate before and after stain resistance is used instead of gray card color comparison;

[0197] 2. Durability

[0198] (1) Artificial weathering test: refer to the artificial weathering test method A specified in GB / T 1865-2009 "Artificial weathering and artificial radiation exposure to filtered xenon arc radiation for paints and varnishes", and test the stain resistance of the test panels after exposure to sunlight for 3 months, artificial accelerated aging (xenon-spray aging) for 200 hours, and immersion in water for 48 hours;

[0199] (2) Bond strength: refer to method 7.17 in JG / T 24-2018 "Synthetic resin emulsion sand-walled architectural coatings" to determine the standard bond strength and bond strength after freeze-thaw cycles;

[0200] 3. Water resistance

[0201] Refer to the method 7.13 in JG / T 24-2018 "Synthetic Resin Emulsion Sand Wall Architectural Paint" for testing (immersion time is 120h), and record the surface conditions of the three test panels prepared in each group. If two of the three test panels do not show coating pathological phenomena such as bulging, cracking, and peeling, and a slight color change is allowed compared with the unimmersed part, it can be evaluated as "no abnormality". If the above coating pathological phenomena occur, describe them according to GB / T 1766.

[0202] Table 1 Performance test results

[0203]

[0204]

[0205] As can be seen from Table 1, the self-cleaning rock flake real stone paint prepared in the present application has a reflection coefficient decrease rate before and after pollution resistance of less than 13%, and the reflection coefficient decrease rate before and after pollution resistance after aging test is still less than 13%, and the bonding strength can reach more than 1.0MPa, which is much higher than the standard requirement (≥0.6MPa), and the bonding strength after 5 freeze-thaw cycles is above 0.7MPa, which is also higher than the standard requirement (≥0.4MPa), and after immersion for 120h, there is no abnormality on the surface, which is higher than the standard requirement of 96h. This shows that the self-cleaning rock flake real stone paint of the present application has strong self-cleaning ability, good stain resistance, and high durability and water resistance. The possibility of losing the super hydrophilic property due to detachment from the substrate or change in surface structure is low.

[0206] The reflectance decrease rate of Examples 4-5 and the reflectance decrease rate after aging test are lower than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, indicating that the present application further controls the addition amount of raw materials used in the real stone paint, which can further improve the stain resistance and durability of the real stone paint.

[0207] The reflectance decrease rate of Examples 6-7 and the reflectance decrease rate after aging test are lower than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, indicating that the present application further adds nanoparticles with high surface energy to the real stone paint, which can further improve the stain resistance and durability of the real stone paint.

[0208] The reflectance decrease rate of Examples 8-9 and the reflectance decrease rate after aging test are lower than those of Example 2, but higher than those of Examples 6-7. The bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, but lower than those of Examples 6-7, indicating that the present application further controls the amount of nanoparticles added, which can further improve the stain resistance and durability of the real stone paint.

[0209] The reflectivity decrease rate and the reflectivity decrease rate after aging test of Example 10 are lower than those of Example 2, but higher than those of Examples 6-7. The bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, but lower than those of Examples 6-7. This shows that the present application uses a mixture of nano zinc oxide and nano aluminum oxide to give full play to the synergistic effect of the two and further improve the stain resistance and durability of the real stone paint.

[0210] The reflectance decrease rate of Examples 11-12 and the reflectance decrease rate after aging test are lower than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, indicating that the present application adopts a mixture of anionic emulsifiers and nonionic emulsifiers as emulsifiers for pure acrylic emulsions, which can improve the hydrophilicity of pure acrylic emulsions, thereby further improving the stain resistance and durability of real stone paint.

[0211] The reflectance decrease rate and the reflectance decrease rate after aging test of Examples 13-14 are lower than those of Example 2, but higher than those of Examples 11-12. The bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, but lower than those of Examples 11-12, indicating that the present application further controls the weight ratio of anionic emulsifiers to nonionic emulsifiers, which can further improve the hydrophilicity of pure acrylic emulsion, thereby further improving the stain resistance and durability of real stone paint.

[0212] The reflectivity decrease rate of Examples 15-17 and the reflectivity decrease rate after aging test are lower than those of Example 2, but higher than those of Examples 11-12. The bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, but lower than those of Examples 11-12. This indicates that the mixed use of sodium salt of alkyl sulfosuccinate and non-ionic emulsifier S90 in this application can give full play to the synergistic effect of the two, thereby further improving the hydrophilicity of the pure acrylic emulsion, and thereby improving the stain resistance and durability of the real stone paint.

[0213] The reflectance decrease rate of Examples 18-19 and the reflectance decrease rate after aging test are lower than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, indicating that the present application further adds gelatinized oxidized starch to the pure acrylic emulsion, which can further improve the cross-linking degree and density of the internal network structure of the pure acrylic emulsion, thereby further improving the stain resistance and durability of the real stone paint.

[0214] The reflectance decrease rate of Examples 20-21 and the reflectance decrease rate after aging test are lower than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, indicating that the present application adopts a mixture of vegetable oil furfuryl ester and ricinoleic acid ethylene glycol monoester as film-forming aids, which can further improve the film-forming effect of real stone paint, thereby further improving the stain resistance and durability of real stone paint.

[0215] The reflectance decrease rate of Examples 22-24 and the reflectance decrease rate after aging test are lower than those of Example 2, but higher than those of Examples 20-21. The bonding strength and the bonding strength after 5 freeze-thaw cycles are higher than those of Example 2, but lower than those of Examples 20-21. This indicates that the present application adopts a mixture of vegetable oil furfuryl ester and ricinoleic acid ethylene glycol monoester, and controls the weight ratio of the two, which can give full play to the synergistic effect of the two, thereby further improving the film-forming effect of the real stone paint, and then improving the stain resistance and durability of the real stone paint.

[0216] The reflection coefficient decrease rate of comparative example 1 and the reflection coefficient decrease rate after aging test are significantly higher than those of Example 2, the bonding strength and the bonding strength after 5 freeze-thaw cycles are significantly lower than those of Example 2, and blistering occurs after immersion for 120 hours, with a blister density level of 2 and a blister size level of S3, indicating that the addition of silicate to the real stone paint in this application can make the real stone paint have higher stain resistance and durability.

[0217] The reflectivity decrease rate of Comparative Example 2 and the reflectivity decrease rate after aging test are significantly higher than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are significantly lower than those of Example 2. Bubbling occurs after immersion for 120 hours, with a bubble density grade of 1 and a bubble size grade of S1, indicating that the pure acrylic emulsion prepared in the present application can make the real stone paint have higher stain resistance and durability than the commercially available pure acrylic emulsion.

[0218] The reflection coefficient decrease rate of comparative examples 3-6 and the reflection coefficient decrease rate after aging test are significantly higher than those of Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are significantly lower than those of Example 2. Bubbling occurs after immersion for 120 hours, with a bubble density level of 1 and a bubble size level of S2. This indicates that the present application adopts a mixed use of potassium silicate and lithium silicate, which can give full play to the synergistic effect of the two, thereby further improving the stain resistance and durability of the real stone paint.

[0219] The reflectivity decrease rate of comparative examples 7-9 and the reflectivity decrease rate after aging test are significantly higher than those in Example 2, and the bonding strength and the bonding strength after 5 freeze-thaw cycles are significantly lower than those in Example 2, and blistering occurs after immersion for 120 hours, with a blister density grade of 1 and a blister size grade of S1, indicating that the pure acrylic emulsion of the present application uses specific hard monomers, soft monomers and cross-linking monomers, which can make the pure acrylic emulsion of the present application have better performance, thereby further improving the stain resistance and durability of the real stone paint.

[0220] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A self-cleaning rock flake real stone paint, characterized in that: The invention comprises white sand, colored sand, rock flakes and a base material in a weight ratio of (350-450): (45-50): (45-55): (480-520); the base material comprises, by weight, 340-354 parts of water, 1.2-1.8 parts of bentonite, 2-3 parts of hydroxyethyl cellulose, 0.2-0.8 parts of a multifunctional additive, 0.8-1.2 parts of a kason fungicide, 4-8 parts of an antifreeze agent, 100-160 parts of a pure acrylic emulsion, 6-12 parts of a film-forming additive, 0.2-0.8 parts of a defoaming agent, 2.5-3.5 parts of a thickener, 1-1.6 parts of a wetting agent, 15-20 parts of potassium silicate, 5-7 parts of lithium silicate, and 3-5 parts of a 4-5wt% sodium tetraborate solution; The pure acrylic emulsion is prepared by the following method: (1) dissolving 4.5-5.0 parts by weight of an emulsifier in 15-16 parts by weight of water, then adding 28-30 parts by weight of methyl methacrylate, 59-61 parts by weight of butyl acrylate, 2-3 parts by weight of acrylic acid, 6-7 parts by weight of diethylene glycol diacrylate and 3-4 parts by weight of hydroxyethyl acrylate, and continuing to stir for 30-40 minutes until a milky white pre-emulsion is obtained; dissolving 0.4-0.5 parts by weight of potassium persulfate in water to obtain a potassium persulfate solution; (2) dissolving 2-3 parts by weight of NaHCO3 in water and heating the mixture to 45-50°C, then adding a pre-emulsion and a potassium persulfate solution, continuing to heat the mixture to 75-80°C, and stirring the mixture for 30-40 minutes; the amount of the pre-emulsion being 10-12% of the total amount of the pre-emulsion obtained in step (1), and the amount of the potassium persulfate solution being 45-50% of the total amount of the potassium persulfate solution obtained in step (1); (3) at a temperature of 75-80°C, the remaining amount of the pre-emulsion and potassium persulfate solution are added dropwise to the product obtained in step (2) within 1-1.5 hours, and then the temperature is raised to 85-90°C, and the reaction is kept at this temperature for 1-1.2 hours, and then cooled to room temperature, filtered, and the pH value is adjusted to 8-9 with aqueous ammonia to obtain a pure acrylic emulsion; The film-forming aid comprises vegetable oleic acid furfuryl ester and ricinoleic acid ethylene glycol monoester in a weight ratio of 1: (1.2-1.5); The vegetable oleic acid furfuryl ester is prepared by the following method: Mix vegetable oleic acid, furfuryl alcohol, cyclohexane, ionic liquid catalyst and sodium hypochlorite, heat to 80-90°C, keep warm for reaction for 3-3.5h, cool to room temperature, filter, adjust pH value to 6-7 with 5-7wt% NaHCO3 solution, stand for stratification, decompress the upper oil layer to obtain vegetable oleic acid furfuryl alcohol ester; n (vegetable oleic acid): n (furfuryl alcohol) is 1: (1.2-1.25), and the weight ratio of cyclohexane, ionic liquid catalyst, sodium hypochlorite and vegetable oleic acid is (2.8-3.0): (0.01-0.02): (0.01-0.02): 1; The ricinoleic acid ethylene glycol monoester is prepared by the following method: Add ricinoleic acid and a solid acid catalyst to 100-110 parts by weight of toluene, mix and stir for 10-15 minutes, then add ethylene glycol and heat to 87-90°C, react for 4-5 hours, then cool to room temperature, adjust the pH value to 6-7 with 3-4wt% NaHCO3 solution, let stand to separate, decompress the upper oil layer and desolventize to obtain ricinoleic acid ethylene glycol monoester; n (ricinoleic acid): n (ethylene glycol) is 1: (1.2-1.3), and the amount of the solid acid catalyst is 1.8-2wt% of ricinoleic acid.

2. The self-cleaning rock flake real stone paint according to claim 1, characterized in that: The base material also includes 7-10 parts by weight of nano zinc oxide and 8-10 parts by weight of nano aluminum oxide.

3. The self-cleaning rock flake real stone paint according to claim 1, characterized in that: The emulsifier comprises an anionic emulsifier and a nonionic emulsifier in a weight ratio of (5-6): (1-2); the anionic emulsifier is sodium salt of alkyl sulfosuccinate, and the nonionic emulsifier is nonionic emulsifier S90.

4. The self-cleaning rock flake real stone paint according to claim 1, characterized in that: In step (3), before cooling, 1.8-2.0 parts by weight of gelatinized oxidized starch is added, and the reaction is continued at the temperature for 1-1.2 hours.

5. A method for preparing the self-cleaning rock flake real stone paint according to claim 1, characterized in that: The following steps are involved: S1. The lithium silicate, wetting agent and pure acrylic emulsion were magnetically stirred for 10-15 min, and then potassium silicate was added dropwise and magnetically stirred for 10-15 min, and then mixed with 4-5wt% sodium tetraborate solution and stirred for 20-30 min to obtain a mixed solution; S2. Bentonite and hydroxyethyl cellulose are added to water while stirring, and then dispersed at a high speed of 1300-1400r / min for 20-30min, and then the speed is reduced to 500-600r / min, and a multifunctional additive, a kasoon fungicide, an antifreeze agent, a mixed solution of step S1, a film-forming aid and a defoaming agent are added, mixed and stirred for 5-10min, and then a thickener is added, and dispersed at a speed of 800-900r / min for 8-10min to obtain a base material; S3. At a rotation speed of 300-310r / min, add white sand, colored sand and rock flakes to the base material of step S2, mix well, and obtain self-cleaning rock flake real stone paint.

6. The method for preparing a self-cleaning rock flake real stone paint according to claim 5, characterized in that: In step S1, 7-10 parts by weight of nano zinc oxide and 8-10 parts by weight of nano aluminum oxide are also added.

Citation Information

Patent Citations

  • Ultra-thin composite slice stone-like coating and preparation method and application thereof

    CN110551431A